Indonesian Language Learning Using Inquiry Approach at MA Nurul Muhajirin Sukatani, Banyuasin Regency - Fatmawaty Fatmawaty (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Learning in Indonesia is the topic of this research. The Inquiry Method in Graduate School According to Nurul Muhajirin Sukatani, who notes that instructors in Indonesia have a wide range of options when it comes to pedagogical techniques, one of them is the inquiry-based model, which encourages students to take an active role in solving issues and gathering data. The sort of research done is qualitative with descriptive features. Interviews, field notes, and other forms of documentation are used to gather information, while data reduction, presentation, and verification are among the steps used during the analysis phase. Data triangulation was utilized to check the reliability of the results in this investigation. The results have been well implemented in learning Indonesian with an Inquiry approach, including task-based inquiry activities, by designing teacher assignments or projects to create engaging, contextual, and relevant learning experiences for students. Discussion and collaboration facilitated by discussion and collaboration that this activity is very beneficial for students. There will be value in cooperation and responsibility when students are given tasks to complete their studies. These group discussions allow students to share ideas, debate, and teach each other. Collaboration will enable students to learn from the perspective of classmates and gain new insights. Contextual learning: this approach helps students understand concepts better and forms a deeper and more relevant understanding. Connecting lessons with students' daily lives makes learning more meaningful and stimulates their interest and motivation to learn.